2014
DOI: 10.1002/pd.4431
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of screening for trisomy 21 in twin pregnancies in first trimester combining nuchal translucency and biochemical markers: a meta‐analysis

Abstract: The results of this meta-analysis show that the accumulative evidence on the performance of the combined test in twin pregnancies is good. Nowadays, it seems to be the best first-trimester screening test available for twin pregnancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 42 publications
0
44
0
Order By: Relevance
“…The DR for Down syndrome may be lower in twin compared with singleton pregnancy. However, a recent meta‐analysis reported similar performance (89% for singletons, 86% for dichorionic twins and 87% for monochorionic twins, at a false‐positive rate (FPR) of 5%) ( EVIDENCE LEVEL: 2++ ).…”
Section: Recommendationsmentioning
confidence: 97%
“…The DR for Down syndrome may be lower in twin compared with singleton pregnancy. However, a recent meta‐analysis reported similar performance (89% for singletons, 86% for dichorionic twins and 87% for monochorionic twins, at a false‐positive rate (FPR) of 5%) ( EVIDENCE LEVEL: 2++ ).…”
Section: Recommendationsmentioning
confidence: 97%
“…In the case of a vanished twin, if there is still a visible fetal pole on ultrasound scan, nuchal translucency alone (combined with maternal age) should be used as serum β‐human chorionic gonadotrophin (β‐hCG) and pregnancy‐associated plasma protein A levels may be affected by the vanishing twin. In this case, cell‐free DNA might also be less accurate, can lead to a false‐positive result, and is generally not recommended …”
Section: Antenatal Care Of Twin Pregnanciesmentioning
confidence: 99%
“…Several clinical studies in high-risk pregnancies and a recent study in a population undergoing routine first-trimester aneuploidy screening have demonstrated that the performance of non-invasive prenatal testing (NIPT) for trisomy 21, with a detection rate of>99% and false-positive rate of <0.1%, is far superior to that of all other currently available screening methods for Down syndrome [6]. Moreover, recent meta-analysis data suggest performance of FTS in twins being inferior to that in singletons, so the false negative rate could be even higher in dichorionic twins accounting for a sensitivity of only 86% [7]. Our case in accordance with recent data is supporting the role of cfDNA testing in screening for trisomy 21 in twins.…”
Section: Discussionmentioning
confidence: 99%